IMPLEMENTASI MODEL PEMBELAJARAN INQUIRY TERBIMBING UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS ANAK USIA DINI - Sri Wahyuni (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Science process skills are scientific skills related to how to obtain information related to scientific objects. In this skill, the child will be stimulated to be able to think logically. This study aims to determine the increase in early childhood science process skills using the guided inquiry learning model. This research is a classroom action research which consists of two cycles. The stages of the research started from planning, implementing, observing, and reflecting. The research subjects were students in TK Tembeng Putik Qur'an, totaling 16 children. The research instrument used was the science process skills observation sheet. Data collection techniques using observation and documentation. Data were analyzed using the percentage formula to determine the increase in children's science process skills. The results showed that the guided inquiry learning model was proven to be able to improve early childhood science process skills. The increase in science process skills in this study was seen in the average value in cycle I of 60.68% and increased in cycle II to 72.14%. This is because every process carried out by children in the guided inquiry learning model supports the improvement of early childhood science process skills. Science process skills on the indicators of using tools and measurements get the highest score compared to other indicators. This happens because early childhood is very happy when invited to participate and be involved in conducting experimental activities. Furthermore, the highest increase in science process skills is found in the communicating indicator. This is because in the guided inquiry learning model, children have carried out experiments directly, so they can make their own conclusions based on the results of their observations.